The Analysis of Students' Misconceptions Using Three Tier-Test Multiple Choice on Ecosystem Material in SMA - Asih, Oktavia Yudhi; Saptono, Sigit (Journal of Biology Education, 2021)
This study aims to analyze high school students' misconceptions using a three-tier multiple-choice test on ecosystem material. The study was conducted SMA Negeri 1 Bawang in the odd semester of the 2020/2021 school year. This research is quantitative descriptive with a sequential explanatory research design. The purposive sampling technique was used to take the research sample. The sample in this study were students in class XI MIPA 1, XI MIPA 2, and XI MIPA 6 SMA Negeri 1 Bawang, with 92 students. The researcher used a three-tier multiple-choice test instrument to analyze SMA Negeri 1 Bawang students' misconceptions on the Ecosystem material by exploring the combination patterns in the students' answers. The results showed that students who experienced misconceptions in the Ecosystem material at SMA Negeri 1 Bawang were 41.16%, categorized as medium. The highest student misconception occurred on Dynamics and Population Density at 70.65% in the medium category. In comparison, the lowest misconception happened in the Food Chain Cases by 25% in the low class. In general, the causes of student misconceptions are students' preconceptions, lack of literature, and lack of time in learning. This research concludes that the three-tier test multiple choice instrument is feasible and practical to analyze students' misconceptions on Ecosystem material.